NO2 Sensor Based on Fe,N-GQDs Modified Three-Dimensional Stacked In2O3 Nanosheet Sensing Material and Its Preparation
Patent Information
- Application Number
- CN202310790499.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-06-30
AI Technical Summary
[0014](1)利用简单的水热法制备出Fe,N-GQDs修饰的三维堆叠In2O3纳米片敏感材料,方法简单,成本低廉;
Smart Images

Figure CN116818849B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor metal oxide gas sensor technology, specifically relating to an NO2 sensor based on Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive material and its preparation method. Background Technology
[0002] In recent years, along with industrial development and the continuous improvement of people's living standards, the emission of harmful gases has exacerbated air pollution problems. Furthermore, nitrogen dioxide (NO2), mainly released from vehicle exhaust and fossil fuel combustion, is a common toxic and harmful gas. NO2 emissions not only lead to acid rain, causing serious negative impacts on water, land, and artificial ecosystems, but also form ground-based photochemical smog, posing a significant threat to human health. Therefore, developing gas sensors for rapid and accurate NO2 monitoring, possessing characteristics such as high sensitivity, high stability, low cost, and miniaturization, is particularly important. In conclusion, finding an appropriate method for detecting NO2 gas is essential.
[0003] Gas sensors based on metal-oxide-semiconductor (MOS) materials have attracted widespread attention due to their solid-state nature, small footprint, and low cost. In₂O₃, with its wider bandgap (3.55-3.75 eV), lower resistance (1 kΩ~160 kΩ), and higher conductivity (over 1000 S / m), has proven to be an ideal material for NO₂ gas sensors. Furthermore, In₂O₃ exists in both hexagonal (H-In₂O₃) and cubic (C-In₂O₃) crystal phases, and its morphology is easily controlled, allowing for interface manipulation through proper design. Graphene quantum dots (GQDs) are considered potential sensing materials due to their quantum size, edge effects, and high conductivity. Through proper design and application, they can be composited with MOS materials (In₂O₃ is a type of MOS), and it is believed that enhanced gas-sensing performance can be achieved by forming heterojunction interfaces. Therefore, 3D-In2O3 nanosheets modified with Fe,N co-doped GQDs (Fe,N-GQDs) can be used for the detection of NO2 gas. Summary of the Invention
[0004] The purpose of this invention is to provide an NO2 sensor based on a three-dimensional stacked In2O3 nanosheet sensitive material modified with Fe,N-GQDs and its preparation method. The sensor obtained by this invention, in addition to high sensitivity, also exhibits a low detection limit and good selectivity.
[0005] The NO2 sensor involved in this invention uses three-dimensional stacked In2O3 nanosheets modified with Fe,N-GQDs as the sensing material. On the one hand, the composite of Fe,N-GQDs and In2O3 forms an 0D / 3D heterogeneous interface, improving the nanoscale interface; on the other hand, the ordered assembly of the nanosheets prevents face-to-face stacking and promotes gas diffusion. In addition, the increase of oxygen vacancies in the material and the co-doping of graphene quantum dots with Fe and N enhance the active sites and reactivity of the material surface. The combined effect of these aspects promotes the reaction efficiency between the sensing material and NO2 gas, improves the material's sensitivity and selectivity, and shortens the response and recovery time. This invention prepares N-GQDs, Fe,N-GQDs, and three-dimensional stacked In2O3 nanosheets separately by hydrothermal method, and then prepares a composite material of Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheets by secondary hydrothermal method to improve the gas-sensing performance of the material. Based on the optimal GQDs doping ratio (0.3 wt%), the In2O3 chemielectric gas sensor can achieve sensitive detection of NO2 gas down to 10 ppb at an operating temperature of 50℃.
[0006] The present invention discloses an NO2 gas sensor based on a three-dimensional stacked In2O3 nanosheet sensitive material modified with Fe,N-GQDs, such as... Figure 1 As shown, the device consists of an Al2O3 ceramic tube substrate with a pair of parallel annular gold electrodes on both sides of its outer surface and two platinum wires connected to each gold electrode, a sensitive material coated on the outer surface of the Al2O3 ceramic tube and the gold electrodes, and a nickel-chromium metal heating coil placed inside the Al2O3 ceramic tube. The sensitive material is a three-dimensional stacked In2O3 nanosheet sensitive material modified with Fe,N-GQDs, and it is obtained by the following steps:
[0007] (1) Add 0.293 g InCl3·4H2O and 1.456 g CTAB to 30 mL of deionized water and stir vigorously for 5 h to make the solution uniform; then add 0.304 g thiourea to the above solution and stir for another hour; transfer the obtained solution to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, seal it well and keep it at 160 ºC for 14 hours; after the reaction is complete and the autoclave cools naturally to room temperature, centrifuge to collect the precipitate and wash it with water and ethanol alternately 6 times; put the obtained product into an oven and dry it at 80°C for 12 hours to obtain a yellow solid powder; transfer the obtained powder to a porcelain boat, place it in a muffle furnace and calcine it in air at 600°C for 2 hours to obtain a three-dimensional stacked In2O3 nanosheet sensitive material;
[0008] (2) Synthesis of Fe,N-GQDs suspension: Dissolve 7-9 mmol citric acid and 23-25 mmol urea in 30-50 mL deionized water, then add 0.4 g FeCl3·6H2O and sonicate for 10-30 min; transfer to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene and maintain at 140-180 ℃ for 5-10 h, collect the obtained precursor, centrifuge at 10000-15000 rpm for 10-30 min, filter the obtained supernatant through a 0.22 μm filter membrane, dry or freeze-dry the filtered product and add deionized water to obtain Fe,N-GQDs suspension with a concentration of 2 mg / mL;
[0009] (3) Disperse 50 mg of the three-dimensional stacked In2O3 nanosheet sensitive material obtained in step (1) and 75 μL of the Fe,N-GQDs suspension obtained in step (2) in 5~20 mL of deionized water and stir for 20~40 min; then transfer the resulting mixture to a 30 mL stainless steel autoclave lined with polytetrafluoroethylene, seal it well, heat it at 120~160 ℃ for 3~6 hours, cool it to room temperature and dry it to obtain Fe,N-GQDs / In2O3 (0.3 wt%) nanosheet sensitive material.
[0010] The present invention discloses a method for preparing an NO2 gas sensor based on Fe,N-GQDs-modified three-dimensional stacked In2O3 nanosheet sensitive material, the steps of which are as follows:
[0011] (1) Take 10~20 mg of Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive material in an agate mortar, add 3~5 drops of ethanol, mix thoroughly and grind into a paste, then take an appropriate amount of paste and coat it evenly on the outer surface of the Al2O3 ceramic tube to form a sensitive material layer of 15~30 μm thickness, and make the sensitive material completely cover a pair of parallel ring gold electrodes on both sides of the outer surface of the ceramic tube; the length of the Al2O3 ceramic tube is 4.0~4.5 mm, the inner diameter and outer diameter are 0.8~1.0 mm and 1.2~1.5 mm, respectively; the width of a single ring gold electrode is 0.4~0.5 mm, and the distance between the two gold electrodes is 0.5~0.6 mm; a platinum wire is led out from the gold electrode, and its length is 4~6 mm;
[0012] (2) The Al2O3 ceramic tube with the sensitive material on the outer surface obtained in step (1) is calcined in air at 200~300 °C for 1.5~3.0 hours to improve the stability of the sensitive material. The heating rate is 3~6 °C / min. After the temperature drops to room temperature, a nickel-chromium alloy heating coil with a resistance of 36~39 Ω is passed through the inside of the ceramic tube as a heating wire. Finally, the above device is welded onto a hexagonal tube base to prepare a side-heated NO2 gas sensor based on Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive material.
[0013] The side-heated NO2 gas sensor based on Fe,N-GQDs-modified three-dimensional stacked In2O3 nanosheet sensing material described in this invention has the following advantages:
[0014] (1) Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive materials were prepared by a simple hydrothermal method. The method is simple and low cost.
[0015] (2) Using CTAB as a structure guiding agent, nanosheets are directionally grown to form three-dimensional stacked In2O3 nanosheets. Then, In2O3 is modified with Fe,N co-doped GQDs, which improves the sensitivity to NO2 gas (414.5-1 ppm) and has good selectivity and low detection limit.
[0016] (3) Commercially available tubular sensors are used. The device process is simple, the cost is low, the size is small, and it is suitable for mass production. Attached Figure Description
[0017] Figure 1 : A schematic diagram of the NO2 side-heated gas sensor based on Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive material as described in this invention;
[0018] Component names: 1. Al2O3 ceramic tube, 2. Platinum wire conductor, 3. Gold electrode, 4. Sensitive material, 5. Nickel-chromium alloy heating coil.
[0019] Figure 2 SEM images of the three-dimensional stacked In2O3 nanosheets, Fe,N-GQDs-doped In2O3 nanosheets (0.3 wt%), and N-GQDs-doped In2O3 nanosheets (0.3 wt%) sensitive materials prepared in Comparative Example 1, Example 1, and Comparative Example 4 of this invention; the nanosheets are approximately 2 μm in size and 30 ~ 40 nm in thickness, and the N-GQDs-doped and Fe,N-GQDs-doped In2O3 nanosheet sensitive materials maintain a good stacked nanosheet structure.
[0020] Figure 3XRD patterns of Fe,N-GQDs-modified three-dimensional stacked In2O3 nanosheets prepared in the comparative and examples of this invention; it can be seen that all sensitive materials belong to the typical cubic In2O3 phase.
[0021] Figure 4 Sensitivity curves of gas sensors prepared in Comparative Examples 1, 2, 1, 3, and 4; the optimal operating temperature of each device is 50 °C, at which the sensitivities to 1 ppm NO2 gas are 100.0, 229.0, 414.5, 262.3, and 294.5, respectively; compared with the sensors in the comparative examples, the sensor in Example 1 has the highest sensitivity to NO2.
[0022] Figure 5 Comparative graphs show the selectivity of gas sensors prepared in Comparative Examples 1, 2, 3, 1, and 4 to different gases at their optimal operating temperatures. This indicates that the sensors in the comparative examples and the actual implementations all exhibit good selectivity for NO2 gas.
[0023] Figure 6 The response / recovery curves of the gas sensors in Comparative Examples 1, 2, 1, 3, and 4 at an operating temperature of 50 °C for 1 ppm NO2 gas are shown. This indicates that compared to Comparative Examples 1 and 4, the response / recovery time of the sensor in Example 1 was reduced by 40.7% / 46.8% and 8.4% / 29.5%, respectively. The response / recovery time decreased when the Fe,N-GQDs content increased to 0.3 wt%, while it increased with increasing Fe,N-GQDs content.
[0024] Figure 7 The response recovery curves of the gas sensor in Example 1 at 50°C for different concentrations of NO2 gas are shown in the inset (the inset is a magnified view of a portion of the curve). This shows that the sensitivity increases significantly with the increase of NO2 gas concentration, and the lower limit of NO2 concentration detected by the sensor is 10 ppb.
[0025] Figure 8 The repeatability curves of the sensors in Comparative Example 1, Example 1, and Comparative Example 4 for 1 ppm NO2 gas at an operating temperature of 50°C show that the sensors have good repeatability.
[0026] Note: The sensitivity (response value) of a device is defined as the ratio of the resistance between its two gold electrodes in the measured gas to its resistance in air. Response and recovery times are the time it takes for the sensor's resistance to reach 90% of the total change after the gas environment in which the device is located is changed (from air to triethylamine gas or from triethylamine gas to air). Testing is performed using a static testing system: the device is placed in a 1-liter gas cylinder containing a specific concentration of the measured gas. The resistance change is observed and recorded, and the corresponding sensitivity and response recovery times are calculated. Detailed Implementation
[0027] Comparative Example 1:
[0028] 1. Three-dimensional stacked In2O3 nanosheets were first synthesized via hydrothermal synthesis and annealing. 0.293 g InCl3·4H2O and 1.456 g CTAB were added to 30 mL of deionized water and stirred vigorously for 5 h to ensure homogeneity of the solution.
[0029] 2. Add 0.304 g of thiourea to the solution obtained in step 1, and stir for 1 hour.
[0030] 3. Transfer the solution obtained in step 2 to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene (PTFE). After sealing well, maintain the autoclave at 160 °C for 14 hours. After the reaction is complete and the autoclave has cooled naturally to room temperature, collect the precipitate by centrifugation and wash it six times alternately with water and ethanol. Place the obtained product in an oven and dry it at 80 °C for 12 hours to obtain a yellow solid powder.
[0031] 4. Transfer the powder obtained in step 3 to a ceramic boat, place it in a muffle furnace, and calcine it in air at 600°C for 2 hours to obtain a three-dimensional stacked In2O3 nanosheet sensitive material.
[0032] 5. Take 15 mg of the sensitive material obtained in step 4 into an agate mortar, add 3 drops of ethanol, mix thoroughly and grind into a paste. Then, take an appropriate amount of the paste and evenly coat it onto the outer surface of the Al2O3 ceramic tube to form a 20 μm thick layer of sensitive material, so that the sensitive material can completely cover the annular gold electrodes on both sides of the outer surface of the ceramic tube. The Al2O3 ceramic tube is 4 mm long, with an inner diameter of 0.8 mm and an outer diameter of 1.2 mm. The width of a single annular gold electrode is 0.45 mm, and the spacing between two gold electrodes is 0.55 mm; a platinum wire with a length of 5 mm is led out from the gold electrode.
[0033] 6. The Al2O3 ceramic tube with the sensitive material coated on its outer surface obtained in step 5 was transferred to a ceramic boat and placed in a muffle furnace. It was calcined in air at 200ºC for 2 hours with a heating rate of 5°C / min to improve the stability of the sensitive material. After the temperature dropped to room temperature, a nickel-chromium alloy heating coil with a resistance of 38 Ω was passed through the inside of the ceramic tube as a heating wire. Finally, the device was welded onto a hexagonal tube base to prepare the NO2 gas sensor of Comparative Example 1.
[0034] Comparative Example 2:
[0035] 1. Three-dimensional stacked In2O3 nanosheets were first synthesized via hydrothermal synthesis and annealing. 0.293 g InCl3·4H2O and 1.456 g CTAB were added to 30 mL of deionized water and stirred vigorously for 5 h to ensure homogeneity of the solution.
[0036] 2. Add 0.304 g of thiourea to the solution obtained in step 1, and stir for 1 hour.
[0037] 3. Transfer the solution obtained in step 2 to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene (PTFE). After sealing well, maintain the autoclave at 160°C for 14 hours. After the reaction is complete and the autoclave has cooled naturally to room temperature, collect the precipitate by centrifugation and wash it six times alternately with water and ethanol. Place the obtained product in an oven and dry at 80°C for 12 hours to obtain a yellow solid powder.
[0038] 4. Transfer the powder obtained in step 3 to a ceramic boat, place it in a muffle furnace, and calcine it in air at 600°C for 2 hours to obtain a three-dimensional stacked In2O3 nanosheet sensitive material.
[0039] 5. Citric acid (8 mmol) and urea (24 mmol) were dissolved in 40 mL of deionized water, and then 0.4 g FeCl3·6H2O was added to the above solution. After sonication for 20 min, the solution was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene and kept at 160 °C for 8 h. The resulting precursor was collected, centrifuged at 12000 rpm for 20 min, and the supernatant was collected and then filtered through a 0.22 μm filter membrane to obtain the Fe,N-GQDs suspension.
[0040] 6. Disperse the In2O3 (50 mg) and 125 μL Fe,N-GQDs suspension (2 mg / mL) obtained in steps 4 and 5 in 10 mL of deionized water and stir for 30 min. Then transfer the mixture to a 30 mL stainless steel autoclave lined with polytetrafluoroethylene, seal it well, heat it at 150 °C for 4 hours, cool it to room temperature and dry it to obtain Fe,N-GQDs / In2O3 (0.1 wt%).
[0041] 7. Take 15 mg of the sensitive material obtained in step 6 into an agate mortar, add 3 drops of ethanol, mix thoroughly and grind into a paste. Then, take an appropriate amount of the paste and evenly coat it onto the outer surface of the Al2O3 ceramic tube to form a 20 μm thick layer of sensitive material, so that the sensitive material can completely cover the annular gold electrodes on both sides of the outer surface of the ceramic tube. The Al2O3 ceramic tube is 4 mm long, with an inner diameter of 0.8 mm and an outer diameter of 1.2 mm. The width of a single annular gold electrode is 0.45 mm, and the distance between two gold electrodes is 0.55 mm. A platinum wire with a length of 5 mm is led out from the gold electrodes.
[0042] 8. The Al2O3 ceramic tube with the sensitive material coated on its outer surface obtained in step 7 was transferred to a ceramic boat and placed in a muffle furnace. It was calcined in air at 200ºC for 2 hours with a heating rate of 5°C / min to improve the stability of the sensitive material. After the temperature dropped to room temperature, a nickel-chromium alloy heating coil with a resistance of 38 Ω was passed through the inside of the ceramic tube as a heating wire. Finally, the device was welded onto a hexagonal tube base to prepare the NO2 gas sensor of Comparative Example 2.
[0043] Comparative Example 3:
[0044] 1. Three-dimensional stacked In2O3 nanosheets were first synthesized via hydrothermal synthesis and annealing. 0.293 g InCl3·4H2O and 1.456 g CTAB were added to 30 mL of deionized water and stirred vigorously for 5 h to ensure homogeneity of the solution.
[0045] 2. Add 0.304 g of thiourea to the solution obtained in step 1, and stir for 1 hour.
[0046] 3. Transfer the solution obtained in step 2 to a 50 mL PTFE-lined stainless steel autoclave, seal well, and maintain at 160 °C for 14 hours. After the reaction is complete and the autoclave has cooled naturally to room temperature, collect the precipitate by centrifugation and wash it six times alternately with water and ethanol. Place the obtained product in an oven and dry at 80 °C for 12 hours to obtain a yellow solid powder.
[0047] 4. Transfer the powder obtained in step 3 to a ceramic boat, place it in a muffle furnace, and calcine it in air at 600 °C for 2 hours to obtain a three-dimensional stacked In2O3 nanosheet sensitive material.
[0048] 5. Citric acid (8 mmol) and urea (24 mmol) were dissolved in 40 mL of deionized water, and then 0.4 g FeCl3·6H2O was added to the above solution. After sonication for 20 min, the solution was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene and kept at 160 °C for 8 h. The resulting precursor was collected, centrifuged at 12000 rpm for 20 min, and the supernatant was collected and then filtered through a 0.22 μm filter membrane to obtain the Fe,N-GQDs suspension.
[0049] 6. Disperse the In2O3 (50 mg) and 25 μL Fe,N-GQDs suspension (2 mg / mL) obtained in steps 4 and 5 in 10 mL of deionized water and stir for 30 min. Then transfer the mixture to a 30 mL stainless steel autoclave lined with polytetrafluoroethylene, seal it well, heat it at 150 °C for 4 hours, cool it to room temperature and dry it to obtain Fe,N-GQDs / In2O3 (0.5 wt%).
[0050] 7. Take 15 mg of the sensitive material obtained in step 6 into an agate mortar, add 3 drops of ethanol, mix thoroughly and grind into a paste. Then, take an appropriate amount of the paste and evenly coat it onto the outer surface of the Al2O3 ceramic tube to form a 20 μm thick layer of sensitive material, so that the sensitive material can completely cover the annular gold electrodes on both sides of the outer surface of the ceramic tube. The Al2O3 ceramic tube is 4 mm long, with an inner diameter of 0.8 mm and an outer diameter of 1.2 mm. The width of a single annular gold electrode is 0.45 mm, and the distance between two gold electrodes is 0.55 mm. A platinum wire with a length of 5 mm is led out from the gold electrodes.
[0051] 8. The Al2O3 ceramic tube with the sensitive material coated on its outer surface obtained in step 7 was transferred to a ceramic boat and placed in a muffle furnace. It was calcined in air at 200 ºC for 2 hours with a heating rate of 5°C / min to improve the stability of the sensitive material. After the temperature dropped to room temperature, a nickel-chromium alloy heating coil with a resistance of 38 Ω was passed through the inside of the ceramic tube as a heating wire. Finally, the device was welded onto a hexagonal tube base to prepare the NO2 gas sensor of Comparative Example 3.
[0052] Example 1:
[0053] 1. Three-dimensional stacked In2O3 nanosheets were first synthesized via hydrothermal synthesis and annealing. 0.293 g InCl3·4H2O and 1.456 g CTAB were added to 30 mL of deionized water and stirred vigorously for 5 h to ensure homogeneity of the solution.
[0054] 2. Add 0.304 g of thiourea to the solution obtained in step 1, and stir for 1 hour.
[0055] 3. Transfer the solution obtained in step 2 to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene (PTFE). After sealing well, maintain the autoclave at 160 °C for 14 hours. After the reaction is complete and the autoclave has cooled naturally to room temperature, collect the precipitate by centrifugation and wash it six times alternately with water and ethanol. Place the obtained product in an oven and dry it at 80 °C for 12 hours to obtain a yellow solid powder.
[0056] 4. Transfer the powder obtained in step 3 to a ceramic boat, place it in a muffle furnace, and calcine it in air at 600°C for 2 hours to obtain a three-dimensional stacked In2O3 nanosheet sensitive material.
[0057] 5. Citric acid (8 mmol) and urea (24 mmol) were dissolved in 40 mL of deionized water, and then 0.4 g of FeCl3·6H2O was added to the solution. After sonication for 20 min, the mixture was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene and kept at 160 °C for 8 h. The resulting precursor was collected, centrifuged at 12000 rpm for 20 min, and the supernatant was collected and filtered through a 0.22 μm filter membrane to obtain Fe,N-GQDs. The synthesis and purification process of N-GQDs was the same as the above steps, except that FeCl3·6H2O was not added.
[0058] 6. Disperse the In2O3 (50 mg) and 75 μL Fe,N-GQDs suspension (2 mg / mL) obtained in steps 4 and 5 in 10 mL of deionized water and stir for 30 min. Then transfer the mixture to a 30 mL stainless steel autoclave lined with polytetrafluoroethylene, seal it well, heat it at 150 °C for 4 hours, cool it to room temperature and dry it to obtain Fe,N-GQDs / In2O3 (0.3 wt%).
[0059] 7. Take 15 mg of the sensitive material obtained in step 6 into an agate mortar, add 3 drops of ethanol, mix thoroughly and grind into a paste. Then, take an appropriate amount of the paste and evenly coat it onto the outer surface of the Al2O3 ceramic tube to form a 20 μm thick layer of sensitive material, so that the sensitive material can completely cover the annular gold electrodes on both sides of the outer surface of the ceramic tube. The Al2O3 ceramic tube is 4 mm long, with an inner diameter of 0.8 mm and an outer diameter of 1.2 mm. The width of a single annular gold electrode is 0.45 mm, and the distance between two gold electrodes is 0.55 mm. A platinum wire with a length of 5 mm is led out from the gold electrodes.
[0060] 8. The Al2O3 ceramic tube with the sensitive material coated on its outer surface obtained in step 7 was transferred to a ceramic boat and placed in a muffle furnace. It was then calcined in air at 200ºC for 2 hours at a heating rate of 5°C / min to improve the stability of the sensitive material. After the temperature dropped to room temperature, a nickel-chromium alloy heating coil with a resistance of 38 Ω was passed through the inside of the ceramic tube as a heating wire. Finally, the device was welded onto a hexagonal tube base to prepare the NO2 gas sensor of Example 1.
[0061] Comparative Example 4:
[0062] 1. Three-dimensional stacked In2O3 nanosheets were first synthesized via hydrothermal synthesis and annealing. 0.293 g InCl3·4H2O and 1.456 g CTAB were added to 30 mL of deionized water and stirred vigorously for 5 h to ensure homogeneity of the solution.
[0063] 2. Add 0.304 g of thiourea to the solution obtained in step 1, and stir for 1 hour.
[0064] 3. Transfer the solution obtained in step 2 to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene (PTFE). After sealing well, maintain the autoclave at 160 °C for 14 hours. After the reaction is complete and the autoclave has cooled naturally to room temperature, collect the precipitate by centrifugation and wash it six times alternately with water and ethanol. Place the obtained product in an oven and dry it at 80 °C for 12 hours to obtain a yellow solid powder.
[0065] 4. Transfer the powder obtained in step 3 to a ceramic boat, place it in a muffle furnace, and calcine it in air at 600°C for 2 hours to obtain a three-dimensional stacked In2O3 nanosheet sensitive material.
[0066] 5. Citric acid (8 mmol) and urea (24 mmol) were dissolved in 40 mL of deionized water. After sonication for 20 min, the mixture was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene and kept at 160 °C for 8 h. The resulting precursor was collected, centrifuged at 12000 rpm for 20 min, and the supernatant was collected and filtered through a 0.22 μm filter membrane to obtain the N-GQDs suspension.
[0067] 6. Disperse the In2O3 (50 mg) and 75 μL N-GQDs suspension (2 mg / mL) obtained in steps 4 and 5 in 10 mL of deionized water and stir for 30 min. Then transfer the mixture to a 30 mL stainless steel autoclave lined with polytetrafluoroethylene, seal it well, heat it at 150 °C for 4 hours, cool it to room temperature and dry it to obtain N-GQDs / In2O3 (0.3 wt%).
[0068] 7. Take 15 mg of the sensitive material obtained in step 6 into an agate mortar, add 3 drops of ethanol, mix thoroughly and grind into a paste. Then, take an appropriate amount of the paste and evenly coat it onto the outer surface of the Al2O3 ceramic tube to form a 20 μm thick layer of sensitive material, so that the sensitive material can completely cover the annular gold electrodes on both sides of the outer surface of the ceramic tube. The Al2O3 ceramic tube is 4 mm long, with an inner diameter of 0.8 mm and an outer diameter of 1.2 mm. The width of a single annular gold electrode is 0.45 mm, and the distance between two gold electrodes is 0.55 mm. A platinum wire with a length of 5 mm is led out from the gold electrodes.
[0069] 8. The Al2O3 ceramic tube with the sensitive material coated on its outer surface obtained in step 7 was transferred to a ceramic boat and placed in a muffle furnace. It was calcined in air at 200ºC for 2 hours with a heating rate of 5°C / min to improve the stability of the sensitive material. After the temperature dropped to room temperature, a nickel-chromium alloy heating coil with a resistance of 38 Ω was passed through the inside of the ceramic tube as a heating wire. Finally, the device was welded onto a hexagonal tube base to prepare the NO2 gas sensor of Comparative Example 4.
Claims
1. A NO2 gas sensor based on a three-dimensional stacked In2O3 nanosheet sensitive material modified with Fe,N-GQDs, comprising an Al2O3 ceramic tube substrate with a pair of parallel annular gold electrodes on both sides of its outer surface and two platinum wires connected to each gold electrode, a sensitive material coated on the outer surface of the Al2O3 ceramic tube and the gold electrodes, and a nickel-chromium metal heating coil placed inside the Al2O3 ceramic tube; characterized in that: The sensing material is a three-dimensional stacked In₂O₃ nanosheet sensing material modified with Fe,N-GQDs, and it is obtained by the following steps. (1) 0.293 g InCl3·4H2O and 1.456 g CTAB were added to 30 mL of deionized water and stirred vigorously for 5 h to make the solution uniform; then 0.304 g thiourea was added to the above solution and stirred for another hour; the resulting solution was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, sealed well and kept at 160 ºC for 14 hours; after the reaction was completed and the autoclave was naturally cooled to room temperature, the precipitate was collected by centrifugation and washed 6 times alternately with water and ethanol; the obtained product was placed in an oven and dried at 80°C for 12 hours to obtain a yellow solid powder; the obtained powder was transferred to a porcelain boat, placed in a muffle furnace and calcined at 600°C in air for 2 hours to obtain a three-dimensional stacked In2O3 nanosheet sensitive material; (2) Dissolve 7-9 mmol citric acid and 23-25 mmol urea in 30-50 mL of deionized water, then add 0.4 g FeCl3·6H2O and sonicate for 10-30 min; transfer to a stainless steel autoclave lined with polytetrafluoroethylene and keep at 140-180 °C for 5-10 h, collect the obtained precursor, centrifuge at 10000-15000 rpm for 10-30 min, filter the obtained supernatant with a 0.22 μm filter membrane, dry or freeze-dry the filtered product and add deionized water to obtain Fe,N-GQDs suspension with a concentration of 2 mg / mL; (3) Disperse 50 mg of the three-dimensional stacked In2O3 nanosheet sensitive material obtained in step (1) and 75 μL of the Fe,N-GQDs suspension obtained in step (2) in 5~20 mL of deionized water and stir for 20~40 min; then transfer the resulting mixture to a stainless steel autoclave lined with polytetrafluoroethylene, seal it well, heat it at 120~160 ℃ for 3~6 hours, cool it to room temperature and dry it to obtain the Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive material.
2. The NO2 gas sensor based on Fe,N-GQDs-modified three-dimensional stacked In2O3 nanosheet sensitive material as described in claim 1, characterized in that: The Al2O3 ceramic tube has a length of 4.0~4.5 mm, an inner diameter of 0.8~1.0 mm, and an outer diameter of 1.2~1.5 mm. The width of a single ring gold electrode is 0.4~0.5 mm, and the spacing between two gold electrodes is 0.5~0.6 mm. Platinum wires with a length of 4~6 mm are led out from the gold electrodes.
3. The method for preparing a NO2 gas sensor based on Fe,N-GQDs-modified three-dimensional stacked In2O3 nanosheet sensitive material as described in claim 2, comprising the following steps: (1) Take 10~20 mg of Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive material prepared in steps (1)~(3) of claim 1 into an agate mortar, add 3~5 drops of ethanol, mix thoroughly and grind into a paste, then take an appropriate amount of paste and coat it evenly on the outer surface of the Al2O3 ceramic tube to form a sensitive material layer of 15~30 μm thickness, and make the sensitive material completely cover the pair of parallel ring gold electrodes on both sides of the outer surface of the ceramic tube; (2) The Al2O3 ceramic tube with the sensitive material on the outer surface obtained in step (1) is calcined in air at 200~300 °C for 1.5~3.0 hours with a heating rate of 3~6 °C / min. After the temperature drops to room temperature, a nickel-chromium alloy heating coil with a resistance of 36~39 Ω is passed through the inside of the ceramic tube as a heating wire. Finally, the above device is welded onto a hexagonal tube base to prepare a side-heated NO2 gas sensor based on Fe,N-GQDs modified three-dimensional stacked In2O3 nanosheet sensitive material.
Citation Information
Patent Citations
Graphene / tin dioxide quantum dot composite material-based NO2 sensor and preparation method thereof
CN106990142A
N-GQDs modified 3DOM In2O3 composite material and preparation method thereof, and application of N-GQDs modified 3DOM In2O3 composite material
CN110736770A